An assessment of translating religious and magical aspects in "Arabian nights" into English - Al-agili, Noor Ghalib Nida; Ahmad, Khatab Mohammad (Edelweiss Applied Science and Technology, 2024)
This thesis discusses the difficulties of translating "Arabian Nights" from Arabic to English, focusing on cultural and religious elements. It analyzes translation strategies from the 19th century to the present by using Katharina Reiss' text typology framework. English translations nevertheless influenced by historical biases and misconceptions. Modern translations show more cultural sensitivity but struggle to fully convey nuances. Market expectations often lead to domestication in translation approaches. The research emphasizes the tension between making the text accessible to Western audiences while keeping its cultural authenticity. It contributes to discussions on literary translation and cultural preservation, emphasizing the need for more complex, culturally aware approaches in translating works across diverse linguistic and cultural landscapes. This study provides insights to inform future translation efforts and cross-cultural literary studies, addressing the difficult balance between reader accessibility and cultural integrity in literary translation.